Investigation on the prevalence of thyroid cancer in Graves’ patients in northeastern part of Turkey: Is surgery a better option for patients with Graves’ disease who develop antithyroid drug-related major adverse events? - Dayanan, R.; Bilen, A.; Demirci, T.; Ciftel, S.; Ciftel, E.; Mercantepe, F.; Bilen, H. (Verduci Editore s.r.l, 2022)
OBJECTIVE: To determine the prevalence of thyroid cancer in Graves’ patients who underwent surgical intervention with and without a history of anti-thyroid drug related major adverse events. PATIENTS AND METHODS: The data of 530 patients with Graves’ disease between 2015 and 2020 were retrospectively reviewed. Preoperative ultrasonography reports and thyroid-stimulating hormone receptor antibody values and postoperative histopathological findings were available for 94 patients that had undergone total thyroidectomy procedure. We compared the prevalence of thyroid cancer between patients with and without a history of anti-thyroid drug related major adverse events. RESULTS: Thyroid cancer was detected in 31 of 94 patients that had undergone total thyroidectomy. Of these patients, 18 had at least one nodule; however, thyroid cancer was incidentally detected in 13 patients without nodule. The 31 patients had the following cancer subtypes: 22 had papillary microcarcinoma, 8 papillary carcinoma and 1 noninvasive follicular thyroid neoplasm with papillary-like nuclear features. While thyroid cancer was present in half of the patients operated owing to anti-thyroid drug-related major adverse event, it was detected in 30% of the patients operated due to other reasons. CONCLUSIONS: In the present study, the prevalence of thyroid cancer among patients with Graves’ disease was found to be much higher than those of other studies in the literature, suggesting that surgery can be considered primarily for the treatment of Graves’ disease. Considering the surgical option in the first plan instead of radioactive iodine therapy appears to be reasonable in patients who develop anti-thyroid drug-related major adverse events. © 2022 Verduci Editore s.r.l. All rights reserved.
Keywords: Antithyroid drug; Graves’ disease; Prevalence; Surgical treatment; Thyroid cancer